The effect of e-learning on the Geography Education students’ levels of understanding at Universitas Veteran Bangun Nusantara - Bayu Kurniaaji; Khabiburrahman Khabiburrahman; Agus Sudargono; Pranichayudha Rohsulina (Journal of Geography Science and Education, 2022)
This study aims to: (1) Find out the effect of e-leaning on the geography education students’ understanding (2) Evaluate the geography education students’ levels of understanding after the use of e-learning. This study was One Group Pretest – Posttest Design. The effect of e-learning on the levels of understanding was measured using pretest and posttest which was continued with analyzing using t-test and statistical description. This study results: (1) There was an effect of e-learning on the geography education students’ levels of understanding in the hydrogeography material which showed with a p.value sig. (2-tailed) at 0.001 (lower than 0.05) and t-statistic value of 4.236 which is greater than t-critical value (4.236 > 1.796), (2). Geography education students’ levels of understanding after the use of e-learning increased as seen from statistical description which showed that 25% students (3 students) is partially understand and occuring misconception which is the rest of 75% (9 orang) students is partially understand without misconception